Strengthening Micro, Small, and Medium Enterprise (MSMES) in Response to the Policies on the Use of Domestic Products: A Case Study in Bekasi City - M. Ikhsan; Taufik Akbar; Abdi Sugiarto (Yayasan Darussalam Bengkulu, 2026)
The study aimed to describe the strengthening of MSMEs carried out by the Bekasi City government in terms of capital, products, and marketing in response to policies on using domestic products within the Bekasi City government. The research used a qualitative approach. Primary data were collected using in-depth interviews with selected informants from local governments, MSMEs, and academia. This research found that the Bekasi City government has made various efforts to strengthen MSMEs in Bekasi through the Dinas Koperasi dan UKM Kota Bekasi (DKUKM Bekasi City), namely 1) socialization and training on home industry food and Pangan-Industri Rumah Tangga (P-IRT) certification are given to the MSMEs; 2) training to improve packaging management capabilities and socialize halal certificates; 3) preparing funds for capital through Bank Syariah Patriot; 4) holding various promotions such as exhibitions, Ramadhan bazaars; and 5) training on making Business Identification Numbers (Nomor Induk Berusaha/NIB), digital marketing, entrepreneurship training or workshops, Home Industry Food Certification (P-IRT), using Shopee for MSMEs, and curation of the MSME products.